Perbaikan Desain Mesin Penanam dan Pemupuk Jagung Bertenega Traktor Tangan - Wawan Hermawan (PERTETA, 2011)
Abstract A prototype of integrated machine for tillage, planting and fertilizer application for corn cultivation powered by hand tractor was modified to improve the planting and fertilizing performances. The fertilizer hopper was redesigned and separated to be two hoppers for urea, and for a mixture of TSP and KCl. The hoppers which had a bigger capacity were placed on left and right sides of the machine. For a better arrangement, the seed hopper was set on the middle part between the fertilizer hoppers. The rotor of fertilizer metering device were redesigned to become an edge cell type rotor, and equipped with a metering cylinder. Materials of the driving wheel were changed by thinner and lighter materials. To improve its driving force, the wheel was equipped by radial lugs and side rims which were set on the main rim. The stationer test result showed that the fertilizer application rate could be varied by setting the rotor opening of the metering device. Capacity of the fertilizer hopper was increased from 5 kg to 12 kg. By modification, the machine weight could be decreased and the vertical load on the handle of the tiller could be decreased from 50 kg (the first prototype) to 31 kg (modified prototype). The application of urea, TSP and KCl could be carried out well, in proper dosage. The theoretical field capacity of the modified prototype was 0.16 ha/hour, and the effective field capacity was 0.13 ha/hour. Keywords: integrated machine, corn planter, fertilizer applicator, modification, performance Abstrak Prototipe mesin pengolah tanah, penanam dan pemupuk jagung terintegrasi dengan tenaga traktor tangan telah dimodifikasi untuk meningkatkan kinerja pananaman dan pemupukannya. Hoper pupuk didesain ulang dan dibagi dua untuk menampung pupuk urea dan campuran pupuk TSP dan KCl. Hoper pupuk dengan kapasitas lebih besar ditempatkan di bagian sisi kiri dan kanan dari mesin. Untuk susunan yang seimbang, hoper benih ditempatkan di tengahnya. Rotor penjatah pupuk dirancang ulang menjadi rotor tipe edge-cell, dan dilengkapi selubung pengatur penjatahan pupuk. Bahan roda penggerak dipertipis dan diperingan. Untuk meningkatkan kemampuan gerak memutarnya, roda tersebut dilengkapi dengan sirip-sirip radial dan pelek samping. Hasil pengujian stasioner menunjukkan bahwa penjatahan pupuk dapat diatur dengan mudah. Kapasitas hoper pupuk meningkat dari 5 kg menjadi 12 kg. Bobot mesin dapat dikurangi, sehingga beban angkat pada stang traktor berkurang dari 50 kg menjadi 31 kg. Pemupukan urea, TSP+KCl dapat dilakukan dengan dosis yang sesuai. Kapasitas lapangan teoritis mesin hasil modifikasi adalah 0.16 ha/jam dan kapasitas lapangan efektifnya adalah 0.13 ha/jam. Kata kunci: mesin terintegrasi, penanam jagung, pemupuk, modifikasi, kinerja Diterima: 23 Agustus 2010; Disetujui: 11 Januari 2011